Iris Feature Extraction Methods Overview - Swati D. Shirke, Ms.; C. Rajabhushanam, Dr. (International Journal of Engineering and Technology, 2018)
Iris reorganization remains one of the superlative recognition techniques in Biometrics system, for human Identification and authentication purpose we can use IRIS Recognition technique by using machine learning technologies. Machine Learning helps us find solutions of many problems in computer vision and recognition techniques [1] .Iris recognition task not only effortlessly but also every day we recognize our friends, relative as well as family members. We also recognition by using persons IRIS pattern composed of a particular combination of features. The main process in IRIS Recognition system is feature learning i.e. a set of techniques that learn feature [2][3]. This Paper deals with: Dimension Reduction techniques for IRIS feature Extraction.Â Â Â